Importance and requirements of implementation of Shari'ah in a secular state - Sulaiman, Kabuye Uthman (2012)
Law and justice are common concepts in political, economic and legal thought. From ancient time to present questions have been and are still being raised about these two concepts and the views of scholars have varied widely. The purpose of this study is twofold; first, to show the relationship between law and justice; and second, to enunciate the requirements for the implementation of the Shari‘ah, Islamic law. While scholars contend that justice is an inherent component of law others argue that justice is simply a moral judgement about law; that “the two are different things, each unrelated to the other”. In this study it is emphasized that law and justice are inseparable. The latter is the objective of the former which means that justice is what the law is there for. Hence some laws can be described as just or unjust.